Simulation fragmentation of samples of rock at explosive loading - Trofimov Vitaly; Shipovskii Ivan (E3S Web of Conferences, 2020)
Research to improve the definition of rational parameters for blasting is becoming increasingly important and valuable. This is especially true in the era of digital technology, which allows miners to realize a holistic vision of optimizing the entire process - from the quarry to the receipt of the final product at the processing plant. The proposed computer simulation based on the Smoothed Particle Hydrodynamics (SPH) method in AUTODYN computer complex to optimize the explosion results by integrating the initial data - charge parameters and rock properties, is aimed at improving measures that reduce the total cost of drilling and blasting, increasing mining productivity and safety. The presented calculations make it possible to estimate the number of fragments and their initial expansion velocity for various explosives.